2010
DOI: 10.1515/jpm.2010.028
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of perinatal complications in children with premature craniosynostosis

Abstract: Children diagnosed with craniosynostosis have a significantly higher rate of numerous birth complications compared to the overall births documented at the Birth Registry of Tyrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Craniosynostosis may interfere with the molding of the skull and preclude a normal birth [6]. Furthermore, infants affected by craniosynostosis are at increased risk of having concomitant complex abnormalities of the upper airway and elevated intracranial pressure [7] and may require ventilatory support or neurosurgical intervention early after birth, thus justifying the need for prenatal diagnosis and counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Craniosynostosis may interfere with the molding of the skull and preclude a normal birth [6]. Furthermore, infants affected by craniosynostosis are at increased risk of having concomitant complex abnormalities of the upper airway and elevated intracranial pressure [7] and may require ventilatory support or neurosurgical intervention early after birth, thus justifying the need for prenatal diagnosis and counseling.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment was highly efficacious for rescuing long bone defects seen in these patients, yet many children still manifested craniosynostosis [26]. Because craniosynostosis develops during fetal or early postnatal life and cannot be reversed without surgery after it has occurred [2729], we hypothesize that treatment must be initiated at earlier developmental time points to affect craniosynostosis.…”
Section: 1 Introductionmentioning
confidence: 99%
“…A retrospective study including 618 cases of isolated craniosynostosis revealed that only 2 cases (0.3%) were known to have been diagnosed prenatally [16]. Although the majority of recent reports on prenatal diagnosis of suture fusion anomalies are related to syndromic cases [17][18][19][20][21], they contribute to detection of nonsyndromic craniosynostosis. Nowadays, different methods can be applied for prenatal diagnosis of craniosynostosis, such as two-dimensional (2D) and three-dimensional (3D) ultrasound, magnetic resonance imaging (MRI), computed tomography (CT) scan and, finally, molecular diagnosis.…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…However, in a retrospective study of fetuses at risk for craniosynostosis, dysmorphology and skull deformity preceded closure of the sutures by 4 to 16 weeks [2]. In a population at risk for this condition, the positive predictive value of direct examination of the sutures may be high, while in low-risk pregnancies it may be minimal, and further investigation may be necessary (3D ultrasound, CT scan or MRI) [2,20].…”
Section: Prenatal Diagnosismentioning
confidence: 99%